Prevalence of short stature in juvenile hypothyroidism and the impact of treatment on various skeletal manifestation and growth velocity in a teritary care center - Manish Gutch; Sukriti Kumar; Syed Mohd Razi; Abhinav Gupta; Surendra Kumar; Keshav Kumar Gupta; Mohit Mohan Singh (Wolters Kluwer Medknow Publications, 2015)
Background: Juvenile hypothyroidism is a very common problem in developing parts of world, and produces various skeletal manifestations. One of them is short stature and it is the most common reason for referral to endocrinologist. Aim and Objectives: To study the prevalence of short stature in juvenile hypothyroidism, to study the various radiological manifestations of juvenile hypothyroidism and to study the impact of treatment on growth velocity and various skeletal manifestations. Materials and Methods: Out of total nine hundred hypothyroid patients, eighty seven patients found to be of juvenile hypothyroidism were enrolled in the study those were 6-18 years of age with newly diagnosed or on follow in the endocrine clinic over a period of 1 ½ years were evaluated clinically and by laboratory tests. Serial assays of TSH, T4, and skeletal X-rays and anthropometry were done at regular interval and clinical and radiological outcome of patients were analyzed. Statistical Analysis: Data were analyzed by SPSS version 17, the P < 0.05 was considered significant. Result: The mean age of diagnosis of juvenile hypothyroidism was 11.2 years, and the females had twice the incidence than that of males, the mean TSH value was 118 ± 24.3 μIU/ml. Prevalence of short stature was found to be 45% while delayed bone age was found to be 72% in juvenile hypothyroid populations. Height SDS increased from -2.9 ± 0.9 at the start of thyroxine therapy to -1.8 ± 0.8 after 12 months (P < 0.001). Bone age SDS increased from 8.9 ± 2.5 at the start of thyroxine therapy to 10.8 ± 2.7 after 12 months. Height of velocity increased from 4.9 ± 0.8 cm/year in the year before treatment to 8.7 ± 1.3 during treatment (P < 0.001). Conclusion: The presentations of juvenile hypothyroidism may be varied; prompt recognition of the findings can lead to early and effective treatment, and improving the skeletal defects.